Non-COVID-19 intensive care admissions during the pandemic: a multinational registry-based study - McLarty, Joshua; Litton, Edward; Beane, Abigail; Aryal, Diptesh; Bailey, Michael; Bendel, Stepani; Burghi, Gaston; Christensen, Steffen; Christiansen, Christian Fynbo; Dongelmans, Dave A; Fernandez, Ariel L; Ghose, Aniruddha; et al. (BMJ Publishing Group Ltd., 2023)
Background: The COVID-19 pandemic resulted in a large number of critical care admissions. While national reports have described the outcomes of patients with COVID-19, There is limited international data of the pandemic impact on non-COVID-19 patients requiring intensive care treatment. Methods: We conducted an international, retrospective cohort study using 2019 and 2020 data from 11 national clinical quality registries covering 15 countries. Non-COVID-19 admissions in 2020 were compared with all admissions in 2019, prepandemic. The primary outcome was intensive care unit (ICU) mortality. Secondary outcomes included in-hospital mortality and standardised mortality ratio (SMR). Analyses were stratified by the country income level(s) of each registry. Findings: Among 1 642 632 non-COVID-19 admissions, There was an increase in ICU mortality between 2019 (9.3%) and 2020 (10.4%), OR=1.15 (95% CI 1.14 to 1.17, p<0.001). Increased mortality was observed in middle-income countries (OR 1.25 95% CI 1.23 to 1.26), while mortality decreased in high-income countries (OR=0.96 95% CI 0.94 to 0.98). Hospital mortality and SMR trends for each registry were consistent with the observed ICU mortality findings. The burden of COVID-19 was highly variable, with COVID-19 ICU patient-days per bed ranging from 0.4 to 81.6 between registries. This alone did not explain the observed non-COVID-19 mortality changes. Interpretation: Increased ICU mortality occurred among non-COVID- 19 patients during the pandemic, driven by increased mortality in middle-income countries, while mortality decreased in high-income countries. The causes for this inequity are likely multi-factorial, but healthcare spending, policy pandemic responses, and ICU strain may play significant roles.